Geroscience approaches to obesity. (17th December 2021) - Bitto, Alessandro; Kaeberlein, Matt
Abstract: Besides aging, obesity is the greatest risk factor for numerous chronic pathologies, including metabolic syndrome, type 2 diabetes, cardiovascular disease, hypertension, and cancer. Preventing and treating obesity would greatly reduce healthcare costs and the impact of the aging process, with estimated savings up to 145, 000, 000, 000. Pharmacological interventions identified by geroscience may prove effective against diet-induced obesity. To test this hypothesis, we fed a 66% kcal/fat diet to nine-month-old C57Bl6/N mice for 6 weeks and treated them with either rapamycin, acarbose, or a combination thereof. Rapamycin, and to a lesser extent acarbose, prevented weight gain and fat accumulation in these mice. We detected increased expression of the Liver Activating Protein (LAP) isoform of the transcription factor CCAT/Enhancer Binding Protein β (C/EBPβ) in the liver of mice treated with rapamycin. C/EBPβ-LAP mediates some of the effects of caloric restriction on nutrient metabolism and increases lifespan in a mouse transgenic model. We tested whether independent activation of C/EBPβ-LAP would recapitulate the effects of rapamycin by treating mice on a high-fat diet with adefovir dipivoxil, a reverse transcriptase inhibitor that can activate LAP in vitro independently of mTOR inhibition. Adefovir dipivoxil reduced weight and fat mass accumulation in mice over the course of 6 weeks. Mice treated with adefovir dipivoxil showed increased expression of genes involved in β-oxidation and lipids mobilization, and reduced activation of fatty acid biosynthesis and lipid storage pathways. Our results identify C/EBPβ-LAP as a potential new target to improve lipid homeostasis in both aging and obesity.